High-standard Farmland Construction and Agricultural Green Low-carbon Transition: Impact Relationship and Mechanism Path Analysis - Liu, Yue (Journal of Global Economy, Business and Finance, 2026)
In order to clarify the mechanism of the role of high-standard farmland construction on the green and low-carbon transformation of agriculture, this study explores the impact of high-standard farmland construction on the green and low-carbon transformation of agriculture and its possible transmission paths based on panel data from 31 provinces using a two-way fixed-effects panel model as well as the super-efficient SBM-GML model that includes undesired outputs. The results show that: 1) the construction of high-standard farmland can significantly promote the green and low-carbon transformation of agriculture, and the conclusion still holds after a series of robustness tests; 2) the results of the mechanism test show that the construction of high-standard farmland mainly helps the green and low-carbon transformation of agriculture by improving the quality of land resources and promoting the use of agricultural socialized services; the scale operation of agriculture plays a positive moderating role in the process of the construction of high-standard farmland to help the green and low-carbon transformation of agriculture; and the scale operation of agriculture plays a positive moderating role in the process of the construction of high-standard farmland to help the green and low-carbon transformation of agriculture. 3) [] Heterogeneity analysis found that the construction of high-standard farmland has a significant positive impact on the eastern part of China, the main grain-producing areas and the main non-grain-producing areas, while the impact on the central and western parts of the country is not obvious. Accordingly, we put forward policy recommendations such as strengthening inputs and policy support for high-standard farmland construction, continuously promoting the use of socialized services and large-scale operation, implementing regional differentiation strategies for different regions, and focusing on improving the construction process in the central and western regions.